THE EFFECT OF USING THE JOINT AUDIT METHOD IN ENHANCING THE QUALITY OF THE EXTERNAL AUDIT REPORT-AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF ACADEMICS AND PROFESSIONAL AUDITORS - Muhannad Abbas Ayash (Scholars Digest Publishing, 2024)
The research aims to demonstrate the effect of using the “joint audit” method in enhancing “the quality of the external audit report,” by identifying the theoretical aspects of the concepts associated with both the joint audit and the external audit report. The researcher based the research hypotheses for the practical side on three factors to demonstrate the extent of the contribution Provided by the “Joint Audit” approach in improving and enhancing the quality of external “audit reports” through: the quality of the audit process when applying the joint audit method, the quality of the audit planning process when applying “joint auditing”, preparing “joint audit” reports and the time of issuing the report. In order to achieve the objectives sought by the research, the researcher conducted a field study through a questionnaire to express the opinions of a sample represented by a group of Iraqi companies, audit offices and auditors, members of the audit committees working in some private Iraqi banks, and a sample of academics in the field of specialization. In order to test the validity of the study’s hypotheses, the researcher reached a set of conclusions, the most important of which is that there is agreement by the research sample that applying the “joint audit” will reduce the delay period in issuing the joint audit report and that this report will be delivered at the specified appropriate time. For him, there is agreement by the research sample that the participation of two auditors in the joint audit process and their discussion of the format of the final joint report submitted will lead to the issuance of a more objective report. The researcher recommended the need to increase interest in developing the joint audit approach through increasing cooperation between audit offices and companies. Major cooperation with emerging offices in order to develop professional practices, especially the joint auditing method.